Strategi Komunikasi Dakwah di Kalangan Mualaf di Daerah Terpencil di Kabupaten Hulu Sungai Utara - Muhni (STIT Syekh Muhammad Nafis Tabalong, 2025)
This research is motivated by the need for effective da'wah communication strategies among converts living in remote areas, particularly in Pulau Damar Village, Banjang District, Hulu Sungai Utara Regency. The geographical conditions, limited access to technology, and the diverse social backgrounds of converts demand da'wah methods that are not only informative but also culturally adaptive. The focus of this research is the da'wah communication strategies implemented by preachers in conveying Islamic teachings to converts in the village. The purpose of this research is to describe the communication approach, the preparation and delivery of da'wah messages, the media used, and the forms of evaluation and follow-up of religious guidance for converts. This research uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The results show that the da'wah communication strategies used are interpersonal, family-based, messages are developed gradually taking into account local language and context, communication media are still dominated by face-to-face and simple media, and the evaluation process is carried out informally through ongoing social interactions. This strategy has proven effective in strengthening the understanding and faith of converts and encouraging the continuation of their Islamic guidance in a socially and spiritually supportive environment.